2019
DOI: 10.1002/jper.19-0443
|View full text |Cite
|
Sign up to set email alerts
|

Experimental gingivitis in patients with and without altered passive eruption

Abstract: BackgroundIndividuals with altered passive eruption (APE) are assumed to be more susceptible to periodontal diseases. To date, this hypothesis has not been sufficiently supported by scientific evidence. The aim of this study, using an experimental gingivitis model, was to examine the development and resolution of gingival inflammation in patients with APE when compared to patients with normal gingival anatomy.MethodsA localized experimental gingivitis was induced in 9 patients with APE (test group) and 9 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Se ha sido evidenciado que la encía de los pacientes con EPA muestran signos de inflamación incluso después de un intervalo de tiempo prolongado en un estudio histológico (9). Incluso, se fundamenta que los pacientes con EPA son más susceptibles a padecer enfermedad periodontal (10). (Tabla 2).…”
Section: Erupción Pasiva Alteradaunclassified
“…Se ha sido evidenciado que la encía de los pacientes con EPA muestran signos de inflamación incluso después de un intervalo de tiempo prolongado en un estudio histológico (9). Incluso, se fundamenta que los pacientes con EPA son más susceptibles a padecer enfermedad periodontal (10). (Tabla 2).…”
Section: Erupción Pasiva Alteradaunclassified
“…12,13 Hasil yang berbeda terkait dengan kurang jelasnya kriteria diagnostik. 14,15 Tahapan penting dalam penatalaksanaan GS adalah mengidentifikasi etiologinya, sehingga dapat ditentukan rencana perawatan dan hasil yang akan dicapai. Pemeriksaan penunjang yang diperlukan untuk mendiagnosis GS dan etiologinya meliputi analisis wajah frontal dan lateral, analisis bibir statis dan dinamis, garis bibir, jarak interlabial dan tampilan gigi seri saat istirahat, dan pemeriksaan periodontal lengkap.…”
Section: Pendahuluanunclassified
“…Together, these two processes determine the position of the DGJ [10]. Clinically, APE is associated with excessive gingival display (gummy smile), short clinical crowns, and predisposition to gingival inflammation [30,31]. The prevalence of APE ranged from 12.1% to 29.5% and was found to be more common in patients with a thick periodontal phenotype [32,33].…”
Section: Altered Passive Eruptionmentioning
confidence: 99%
“…However, it was suggested that bone sounding could be challenging in patients with APE, due to the long tightly attached epithelium and the proximity of the buccal bone crest to the CEJ (in subtype B) [44]. In summary, though several approaches exist, most experts agree that a facial negative GR of ≥3 mm is indicative of APE [11,30,33].…”
Section: Altered Passive Eruptionmentioning
confidence: 99%